Financial Literacy and Investment Decisions: A Study of Salaried Individuals in Kathmandu - Sharma , Tenzina; Pokharel, Ankit (Adhyayan Journal, 2025)
Financial literacy refers to an individual's capacity to comprehend financial concepts, analyze financial information, and make informed financial decisions to attain financial objectives. This paper explores the relationship of financial literacy with the investment decisions made by salaried individuals in Kathmandu. It examined the effect of financial knowledge, financial attitude, and financial awareness on investment decisions. It explained whether there are any biases in terms of gender, monthly income, employment sector, employment level, and marital status when making investment decisions. A well-structured, close-ended questionnaire was conducted among 200 salaried people of Kathmandu working in different sectors. Analysis has been done using a hierarchical multiple regression model. The results show that financial attitude and financial awareness have a positive and significant impact on investment decisions. Surprisingly, financial knowledge, being positively correlated, does not have a substantial effect on investment decisions.None of the controlled variables were found to influence investment decisions significantly. Hence, financial attitude and awareness play a crucial role in salaried people's investment decisions.